Percepción de la especialidad de Etología (aplicada en caninos) en los veterinarios de los cantones de Guayaquil y Samborondón. - Rumbea Ruiz, Paola Gabriela (2019)
Sometimes, animals show behavioral problems that are not caused by any underlying disease, and that may be a source of distress for themselves, or cause trouble to people or other animals. However, not every veterinarian is sufficiently capable of personally handling those issues, or has knowledge on the existence of specialists who are qualified to give the correct treatment. The objective was to analyze the perception of the veterinarians of Guayaquil and Samborondón on the branch of Ethology. A survey about animal Ethology was conducted among 103 veterinarians in several facilities located in Guayaquil and Samborondón. After processing the gathered data from three groups of questions, it was possible to calculate scores to obtain: the level of importance attributed to Ethology; the percentage and level of qualification of veterinarians on this specialty; and which percentage of them actually apply, to some extent, this subject on their everyday clinical practice. Results were obtained, in a similar way, for each surveyed sector within the two cantons. The most relevant results were: 1) surveyed professionals associated a regular level of importance to the branch of Ethology; 2) more than half the veterinarians (66.02) claimed to have received some degree of training in animal behavior; the general qualification level obtained was “high”; 3) The general application of Ethology to everyday clinical practice happened to a regular extent.